2007
DOI: 10.1158/0008-5472.can-07-1294
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation Predisposes Nonmalignant Human Mammary Epithelial Cells to Undergo Transforming Growth Factor β–Induced Epithelial to Mesenchymal Transition

Abstract: Transforming growth factor B1 (TGFB) is a tumor suppressor during the initial stage of tumorigenesis, but it can switch to a tumor promoter during neoplastic progression. Ionizing radiation (IR), both a carcinogen and a therapeutic agent, induces TGFB activation in vivo. We now show that IR sensitizes human mammary epithelial cells (HMEC) to undergo TGFB-mediated epithelial to mesenchymal transition (EMT). Nonmalignant HMEC (MCF10A, HMT3522 S1, and 184v) were irradiated with 2 Gy shortly after attachment in mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
130
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 45 publications
7
130
1
Order By: Relevance
“…The radiationinduced phenotypic heterogeneity, we report, might reflect transient cellular plasticity as well as stress-evoked responses of preexistent subsets cells seen in the parental DU145 and PC-3 cell populations. [40][41][42][43][44][45][46][47][48][49][50][51][52] Ionizing radiation can promote traits of EMT in normal human mammary epithelium, 41 lung carcinoma 42,43 and colorectal cancer cells. 44 Furthermore, besides their role in E-cadherin repression, 45,46 Slug and Snail have been implicated in radioresistance-associated EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The radiationinduced phenotypic heterogeneity, we report, might reflect transient cellular plasticity as well as stress-evoked responses of preexistent subsets cells seen in the parental DU145 and PC-3 cell populations. [40][41][42][43][44][45][46][47][48][49][50][51][52] Ionizing radiation can promote traits of EMT in normal human mammary epithelium, 41 lung carcinoma 42,43 and colorectal cancer cells. 44 Furthermore, besides their role in E-cadherin repression, 45,46 Slug and Snail have been implicated in radioresistance-associated EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the absence of the EMT-inducing signals received from the activated stroma that are present in primary tumors, metastatic cancer cells may simply fall back to an epithelial state when entering into sites of dissemination (84,85). However, some studies found that the induction of an EMT seemed to be able to create a heritable state, even long after the EMT-inducing stimulus was removed (86). Furthermore, increasing evidence suggests that the EMT process is greatly associated with resistance to chemotherapy, radiotherapy, and even targeted therapy (see the "Clinical importance of EMT and MET" section).…”
Section: Microenvironment and Changes In Cell Phenotypementioning
confidence: 99%
“…Several signaling pathways are also reported to be associated with EMT, which lead to transcriptional and post-transcriptional induction of EMT transcription factors (23). In regard to the relationship between irradiation and EMT, Andarawewa et al reported that irradiation induced TGF-β-mediated EMT (24). Several studies have examined the possible role of EMT in CRC progression (25,26), and the association between chemoresistance and EMT in CRC (27)(28)(29).…”
mentioning
confidence: 99%